Stability studies of hybrid TiO2 based nanofluids - Wong, Sze Yin; Radhiyah, Abd Aziz (Penerbit UMP, 2021)
This article studies the stability of hybrid TiO2 based nanofluid by varying the ultra-sonication time, weight fraction between carbon and TiO2 and type of surfactant. The objective of this research are synthesise volume fraction of 0.1% C - TiO2 hybrid nanofluid with 15ml of distilled water and study the effect of weight fraction between C and TiO2, type of surfactant and ultra-sonication time to the stability of hybrid nanofluid. Weight fraction between C – TiO2 will be varied at 0% - 100%, 10% - 90%, 50% - 50%, 90% - 10% and 100% - 0%. Different ultrasonication time will be used which are 1, 3 and 5 hours to determine the optimum ultrasonication time for the hybrid nanofluid. Sodium dodecyl sulphate (SDS) and Triton X-100 will be added into hybrid nanofluid to determine the effect of surfactant to the stability of hybrid nanofluid. The morphology and particle size characteristic of TiO2 and carbon powder is evaluated by using X-ray diffraction and FESEM. It is shown that TiO2 has particle size of around 30nm while carbon powder used is flat shaped. In this research, two steps method is used to synthesise the hybrid nanofluid. After mixing the two powder together, it will be mixed with distilled water by magnetic stirring for 3 hours. Then ultrasonication is included in synthesise of hybrid nanofluid to prevent agglomeration of particles. The pH values of each hybrid nanofluid is measured by using pH meter. Two stability evaluations are carried out which are centrifugation and zeta potential measurement. Centrifugation is carried out right after hybrid nanofluid is done ultra-sonicated for 30 minutes at 2000 RPM. Hybrid nanofluid that is ultra-sonicated for 3 hours resulted to achieve highest stability with highest value of zeta potential of -21.8 mV. 100% C - 0% TiO2 hybrid nanofluid has the highest zeta potential measurement of -37.6 mV. Finally, for type of surfactant, SDS able to enhance stability of hybrid nanofluid more than Triton X-100. The zeta potential of hybrid nanofluid after addition of SDS reached -47.0 mV which is higher than Triton X-100 which only achieve zeta potential measurement of -24.3 mV.